A partial botanical survey of a gamepreserve - Győri, Judit; Kovács, Szilvia; Rédei, Károly; Juhász, Lajos; Szendrei, László (Acta Agraria Debreceniensis, 2012)
Hungary is internationally well known for its high level game management. An important part of game management is indoor game keeping. In Hungary more and more game preserves were founded all over the country. The role of these game preserves to retain forest stands outside of the closed area. According to the law, in the game-preserves the game bearing capacity is not the most important parameter, because in these areas the feeding is continuous. In practice it means that in game-preserves we find a much higher density of games than in nature. This causes a relative big loading of the area (of the herbaceous and arboreal), where the game-preserves are located. Our aim is to study the ecological and management issues of forest- and game resources. The scene of these work is a game-preserve related to the Nyírerdő Corporation (Nyíregyháza).We have done a botanical survey (plant coverage, life-form spectrum) in the three previous units and in the control area (outside of the game-preserve) as well. Our results show the difference in case of the state of herbaceous plants between areas with higher and lower game density.